Pumilio proteins utilize distinct regulatory mechanisms to achieve complementary functions required for pluripotency and embryogenesis - Uyhazi, Katherine E. (Proc Natl Acad Sci U S A, 2020)
Gene regulation in embryonic stem cells (ESCs) has been extensively studied at the epigenetic-transcriptional level, but not at the posttranscriptional level. Pumilio (Pum) proteins are among the few known translational regulators required for stem-cell maintenance in invertebrates and plants. Here we report the essential function of two murine Pum proteins, Pum1 and Pum2, in ESCs and early embryogenesis. Pum1/2 double-mutant ESCs display severely reduced self-renewal and differentiation, and Pum1/2 double-mutant mice are developmentally delayed at the morula stage and lethal by embryonic day 8.5. Remarkably, Pum1-deficient ESCs show increased expression of pluripotency genes but not differentiation genes, whereas Pum2-deficient ESCs show decreased pluripotency markers and accelerated differentiation. Thus, despite their high homology and overlapping target messenger RNAs (mRNAs), Pum1 promotes differentiation while Pum2 promotes self-renewal in ESCs. Pum1 and Pum2 achieve these two complementary aspects of pluripotency by forming a negative interregulatory feedback loop that directly regulates at least 1,486 mRNAs. Pum1 and Pum2 regulate target mRNAs not only by repressing translation, but also by promoting translation and enhancing or reducing mRNA stability of different target mRNAs. Together, these findings reveal distinct roles of individual mammalian Pum proteins in ESCs and their essential functions in ESC pluripotency and embryogenesis.